2012
DOI: 10.1111/j.1748-1716.2012.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

No direct role for A1/A2 adenosine receptor activation to reflex cutaneous vasodilatation during whole‐body heat stress in humans

Abstract: These data suggest A1/A2 adenosine receptor activation does not directly contribute to cutaneous active vasodilatation; however, a role for A1/A2 adenosine receptor activation is unmasked when NO synthase is inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…As Cheng et al (1996) demonstrated a tone-dependent effect of adenosine on vessel opening, it is not unreasonable to propose that the different baseline thermal status (i.e. following cooling in the present study, and from normothermia in the study by Fieger & Wong, 2012) contributed to the slight differences in findings. Further research is warranted to examine this possibility, because no tone-dependent effects have been demonstrated in human skin.…”
Section: Adenosine and Cutaneous Vasodilatationcontrasting
confidence: 42%
See 2 more Smart Citations
“…As Cheng et al (1996) demonstrated a tone-dependent effect of adenosine on vessel opening, it is not unreasonable to propose that the different baseline thermal status (i.e. following cooling in the present study, and from normothermia in the study by Fieger & Wong, 2012) contributed to the slight differences in findings. Further research is warranted to examine this possibility, because no tone-dependent effects have been demonstrated in human skin.…”
Section: Adenosine and Cutaneous Vasodilatationcontrasting
confidence: 42%
“…The theophylline concentration used was based on that reported by Fieger & Wong (2010, 2012, while that for L-NAME was chosen based on previous studies (Minson et al 2001;Fieger & Wong, 2010). Infusions were maintained for a 45 min period to ensure the establishment of each blockade (Minson et al 2001;Fieger & Wong, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximal cutaneous vasodilation was elicited via infusion of sodium nitroprusside (SNP) at a rate of 2 l/min and increasing the temperature of the local heating units to 43°C. This temperature increase and dose of SNP have been previously determined effective in eliciting a maximal skin blood flow response (6,7,11,(27)(28)(29).…”
Section: Ethical Approval the Institutional Review Board At Kansas Smentioning
confidence: 98%
“…We, and others, have previously shown a 10 mM concentration of L-NAME adequately inhibits NOS in human skin (6,7,11,20,21,(27)(28)(29), and this duration of EMLA cream inhibits sensory nerve function (10,21,22). All drug treatments were dissolved in lactated Ringer (Baxter Healthcare; Deerfield, IL) and were perfused at a constant rate of 2 l/min with a microinfusion pump (Bee Hive controller and Baby Bee Syringe Pumps; Bioanalytical Systems, West Lafayette, IN).…”
Section: Ethical Approval the Institutional Review Board At Kansas Smentioning
confidence: 99%